SECRETOLYTIC THERAPY EFFICIENCY FOR COMPLEX TREATMENT OF ACUTE BACTERIAL SINUSITIS FOR STAY IN CHILDREN PATIENTS - Yu.L. Soldatskiy; E.K. Onufrieva; S.F. Gasparyan (Union of pediatricians of Russia, 2008)
The study analyzes the effectiveness of combined plant based preparation for complex therapy of in patient children with acute bacterial sinusitis. The main patient group was comprised of 75 patients that received traditional treatment with additional secretolytic therapy, the control group consisted of 83 children (the groups were statistically comparable). According to the research data, prescribing the medication improves treatment efficiency on a statistically valid level: fewer procedures are needed for pus evacuation, and clinical recovery is faster. It should be noted that treatment efficiency is not dependant on which secretolytic form is used - pills or drops.Key words: acute bronchial sinusitis; childhood.